2016
DOI: 10.1073/pnas.1604299113
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role for amyloid precursor protein in adult experience-dependent plasticity

Abstract: Changes in neural circuits after experience-dependent plasticity are brought about by the formation of new circuits via axonal growth and pruning. Here, using a combination of electrophysiology, adeno-associated virus-delivered fluorescent proteins, analysis of mutant mice, and two-photon microscopy, we follow long-range horizontally projecting axons in primary somatosensory cortex before and after selective whisker plucking. Whisker plucking induces axonal growth and pruning of horizontal projecting axons fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In light of our results, we propose that APP-DR6 contribute to neurodegeneration via a β-secretase-dependent non-cell autonomous scenario, which is in contrast with the β-secretase-independent cell autonomous scenario put forward in the axonal homeostatic situations 32 , 34 , 53 , 54 . Given the role of DR6 in axonal pruning during development, surprisingly but importantly, DR6 silencing in our in vivo model of ALS protected against the loss of MN cell bodies but was less effective in mitigating motor axon damage (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In light of our results, we propose that APP-DR6 contribute to neurodegeneration via a β-secretase-dependent non-cell autonomous scenario, which is in contrast with the β-secretase-independent cell autonomous scenario put forward in the axonal homeostatic situations 32 , 34 , 53 , 54 . Given the role of DR6 in axonal pruning during development, surprisingly but importantly, DR6 silencing in our in vivo model of ALS protected against the loss of MN cell bodies but was less effective in mitigating motor axon damage (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…As mentioned above, of the three significant ligand–receptor pairs identified by SEARCHIN, we began our experimental validation by studying the role of APP and DR6 in our ALS models, as APP–DR6 interaction has been previously validated 32 34 and proposed in a few neurobiology-relevant phenotypes. For instance, APP-DR6 emerged as instrumental to axonal pruning during development 32 , 34 and both DR6 and APP are critical for axonal plasticity in adult mice 53 , 54 . In addition, it was reported that APP-DR6 has a role in the pathophysiology of Alzheimer’s disease 32 , a view that could not be confirmed 33 .…”
Section: Discussionmentioning
confidence: 99%
“…While previously described APPL d null mutant phenotypes suggest a role for APPL in axon growth and synaptogenesis (Torroja et al, 1999b; Mora et al, 2013; Soldano et al, 2013), interaction of vertebrate APP with the Death Receptor 6 has been suggested to cell-autonomously also regulate axonal pruning (Nikolaev et al, 2009; Kallop et al, 2014; Olsen et al, 2014; Marik et al, 2016). Our finding that APPL is retrogradely transported, implies a role for APPL at the GF terminals.…”
Section: Resultsmentioning
confidence: 99%
“…APPL processing and trafficking of the full-length protein and fragments is distinctive in different types of neurons (Torroja et al, 1996; Ramaker et al, 2016) and with respect to its functional roles in neurite growth (Singh and Mlodzik, 2012; Mora et al, 2013; Soldano et al, 2013; Singh et al, 2017), synapse formation (Torroja et al, 1999b), and in pruning of GF as well (Figure 4A). Death Receptor 6 has been suggested to regulate axonal pruning via its interaction with vertebrate APP (Nikolaev et al, 2009; Kallop et al, 2014; Olsen et al, 2014; Marik et al, 2016). Therefore, altered signaling at the plasma membrane or defective sorting of a tumor necrosis factor receptor may cause the observed degenerative phenotypes in some but not all cell types of APPL-SD expressing animals.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ is well known for causing pathological dysregulation of postsynaptic trafficking of both the AMPA [39] and N -Methyl- d -aspartate (NMDA) [40]-type glutamate receptors. Notably, APP also has physiological roles in the function and trafficking of these glutamate receptors [41,42,43] and may thus be important for synaptic plasticity and learning/memory [44,45,46,47,48]. The actions of APP at the synapse are also known to be mediated by the secreted (s)APPs, mainly sAPPα generated by α-secretase cleavage [49,50,51,52,53].…”
Section: Introductionmentioning
confidence: 99%